Effects of laser peening on fretting wear behaviour of alloy 718 fretted against two different counterbody materials. (October 2017) - Anand Kumar, S; Sundar, R; Ganesh Sundara Raman, S; Gnanamoorthy, R; Kaul, R; Ranganathan, K; Bindra, K S
This paper deals with the effects of laser peening on fretting wear behaviour of a nickel-based superalloy, alloy 718, fretted against two different counterbody materials (alumina and SAE 52100 steel). Laser peening was carried out on alloy 718. Microstructural characterization of laser peened surface was done by electron back-scattered diffraction and transmission electron microscopy. Surface roughness, nanoindentation hardness, and residual stress of both laser peened and unpeened samples were determined. Fretting wear tests were conducted on unpeened and laser peened samples using two different counterbody materials (alumina and SAE 52100 steel balls). The results show that nanocrystallites formed in the surface and near-surface regions and compressive residual stress were induced after laser peening. Hardness increased due to grain refinement at the surface and near-surface regions. There was no significant change in the surface roughness. The laser peened sample exhibited lower tangential force coefficient values compared to unpeened samples at all loads, which may be attributed to higher hardness. Samples fretted against alumina counterbody exhibited higher tangential force coefficient compared to samples fretted against steel counterbody. Owing to increased surface hardness and higher compressive residual stress, laser peened samples exhibited lower fretting wear damage compared to unpeened samples. Due to tribochemical reactions, the wear volume of unpeened and laser peened samples fretted against alumina counterbody was higher than that of the samples fretted against steel counterbody.